1986
DOI: 10.1152/ajpheart.1986.251.1.h109
|View full text |Cite
|
Sign up to set email alerts
|

Vascular hyperresponsiveness in perfused lungs from monocrotaline-treated rats

Abstract: Studies were conducted in isolated, buffer-perfused lungs to determine whether altered pulmonary vascular responsiveness could contribute to the evolution of monocrotaline (MCT)-induced pulmonary hypertension. Adult male rats were given a single subcutaneous injection of either 105 mg/kg MCT or its vehicle and vascular responsiveness to angiotensin II, ventilatory hypoxia (3% O2), and KCl was assessed in isolated, buffer-perfused lungs at 4, 7, and 14 days post-treatment. Relative to preparations derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…In the isolated perfused lung, Gillespie et al (1986) demonstrated that pulmonary vascular responsiveness to angiotensin II, but not high KCl, was augmented in MCT-treated rats at days 4 and 7, but not at day 14. Our findings of decreased PHE-induced pulmonary artery contraction on day 28 after MCT treatment are consistent with this report, and suggest that, although some enhanced responsiveness may occur before development of PH, this early alteration may not contribute to the sustained elevation in pulmonary arterial pressure.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In the isolated perfused lung, Gillespie et al (1986) demonstrated that pulmonary vascular responsiveness to angiotensin II, but not high KCl, was augmented in MCT-treated rats at days 4 and 7, but not at day 14. Our findings of decreased PHE-induced pulmonary artery contraction on day 28 after MCT treatment are consistent with this report, and suggest that, although some enhanced responsiveness may occur before development of PH, this early alteration may not contribute to the sustained elevation in pulmonary arterial pressure.…”
Section: Discussionmentioning
confidence: 93%
“…Large vessels such as the aorta, skeletal muscle, and diaphragmatic and mesenteric arterioles could be affected (Doyle and Walker, 1991;Kuwahira et al, 1993;Toporsian and Ward, 1997;Auer and Ward, 1998). Although MCT treatment may cause both pulmonary and systemic vascular inflammation and endothelial damage, MCT-treated rats have been used as a model of progressive lung injury and PH (Gillespie et al, 1986;Fullerton et al, 1996). In our hypoxia and MCT models of PH, we found no changes in the responsiveness of the mesenteric vessels jpet.aspetjournals.org to vasoconstrictor or vasodilator stimuli, indicating specific changes in the pulmonary but not the systemic circulation in experimental PH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have shown that PH in hypoxic and MCT-treated rats is associated with reduced pulmonary responsiveness to vasoconstrictors and endogenous and exogenous nitrovasodilators (2,25,27,50,67) and extensive pulmonary arteriolar thickening and remodeling (9,12,44,50,53,59). Multiple mechanisms may contribute to pulmonary vascular remodeling in PH including resident medial pulmonary VSMC hypertrophy and hyperplasia and a phenotypic switch from a contractile to a synthetic phenotype; transdifferentiation of circulating and resident progenitor, adventitial, or endothelial cells to a VSMC-like phenotype; and intimal and adventitial changes.…”
Section: Discussionmentioning
confidence: 97%
“…12 Furthermore, the RAS is known to respond to pathologic alterations in cardiac performance. 3 Adult humans 4 and probably children 3 show a stimulation in RAS activity with congestive heart failure.…”
Section: T He Renin-angiotensin System (Ras) Is Thoughtmentioning
confidence: 99%